2003
DOI: 10.1046/j.1365-2648.2003.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and sexual orientation: relationship to mental well‐being and functional health status

Abstract: The regression analysis showed that spirituality, sexual orientation, age and HIV symptoms contributed significantly to mental well-being and functional health status. Further research is needed to explore the various ways that sexual orientation influences health status findings in those with HIV disease in certain segments of the population. The findings support the inclusion of spirituality as a variable when examining mental well-being and physical health. Finally, given the limitations of the design, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
1
32
0
2
Order By: Relevance
“…Our findings echo those from earlier studies that showed that greater levels of spirituality were associated with health outcomes such as fewer mental health problems, fewer reported HIV-related symptoms, and better overall HRQoL in people with HIV/AIDS. 13,14,21,22,39 Previous studies have found that people with HIV/AIDS often use religious coping (defined as how a person uses their spirituality/religion to manage a difficult situation) to find a sense of meaning/purpose in life, to Italics indicate independent variables significant in 4 or more of the models. Ã VA vs Non-VA. cope with issues of guilt and shame, and to deal with grief and bereavement associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings echo those from earlier studies that showed that greater levels of spirituality were associated with health outcomes such as fewer mental health problems, fewer reported HIV-related symptoms, and better overall HRQoL in people with HIV/AIDS. 13,14,21,22,39 Previous studies have found that people with HIV/AIDS often use religious coping (defined as how a person uses their spirituality/religion to manage a difficult situation) to find a sense of meaning/purpose in life, to Italics indicate independent variables significant in 4 or more of the models. Ã VA vs Non-VA. cope with issues of guilt and shame, and to deal with grief and bereavement associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…13,19,20 Furthermore, previous studies have been limited by small sample sizes, crosssectional design, single site recruitment, and a single-item or single-measure for religion/spirituality. 4,8,21 For example, a study by Coleman and Holzemer of 177 African American men and women with HIV assessed spiritual well-being, 22 but did not examine other important spiritual/religious indicators such as the use of religious coping or the level of intrinsic religiosity. Other studies have utilized relatively smaller, nongeographically diverse samples with sample sizes ranging from 10 to 275, 2,7,15 limiting the generalizability of findings to samples outside those specific geographic regions or demographic make-ups.…”
mentioning
confidence: 99%
“…18,19,41 Spiritual well-being, or a sense of purpose/meaning and personal connectedness to a higher power or truth, may enhance physical and mental health through biological, psychological, and social mechanisms. 20 Greater spiritual well-being may facilitate more positive and ''healthy'' personal and social behaviors, may provide an overarching and unifying framework with which to deal with unexpected and difficult situations, and may give a greater sense of coherence between the individual and their environment, all of which may provide protection against depression or other psychological problems.…”
Section: Commentmentioning
confidence: 99%
“…In another study, individuals with spiritual practices have displayed lower rates of suicide and substance addiction [34]. Researches have commented that those mentioned positive effects should depend on their power to relieve patients' pain and anxiety, to comfort them physiolocially, psychologically and mentally and to enhance communication [4,[33][34][35][36][37][38]. Regarding the studies, spiritual care has been included in the Professional Nursing Practice Standards of Care Tanzania, Canada and the United States.…”
Section: Spırıtualıty and Its Impact On The Recovery Of Patıentsmentioning
confidence: 99%
“…are, the more open their spiritual care perceptions will be [35][36][37][38]40]. According to a study by Stang et al [41] in Switzeland, though the most of nurses (98%) consider spiritual care as necessary, only half of them (48%) provide spiritual care.…”
Section: Spırıtualıty and Its Impact On The Recovery Of Patıentsmentioning
confidence: 99%